Microbiota profile of Malaysian kefir grain and anti-metastatic effects of kefir water in murine breast cancer cells - Zamberi, Nur Rizi (2016)
Breast cancer is the leading cancer in women where metastasis is the major cause of breast cancer death. For years, a cure for cancer is still being researched on and the inhibition of metastasis cascade is one of the goals. The association of functional food such as probiotics with cancer therapy has become an emerging field of study. Kefir is a uniquely cultured product and traditionally used as a daily serving in Eastern Europe for its health benefits. Reports have shown that kefir has health-promoting benefits such as giving rise to antioxidants, stimulates immune response and possesses antitumor properties. Recently, it has gained popularity in Asian countries including Malaysia. This study aims to detect microbial diversity present in kefir grain using 16S metagenomic approach, evaluates its antioxidant potential and assesses the antimetastatic effect of kefir towards murine breast cancer model in vitro and in vivo. The microbial diversity in kefir water was determined by using Next-Generation Sequencing (NGS) and antioxidant assays were performed to evaluate the antioxidant potential of kefir water. In vitro and in vivo anti-metastasis studies of 4T1 murine breast cancer cells were further investigated. Lactobacillus genus was the dominant genus detected in the kefir grain where the predominant species was L. kefiranofaciens while L. kefiri was the second in abundance. Kefir water displayed prominent antioxidant activities and gallic acid (0.816  0.11 μg/mg) was detected in the HPLC profile. Kefir water was cytotoxic towards 4T1 cells in vitro and further in vitro assessment on metastasis was evaluated using wound healing assay, in vitro migration and invasion assay and mouse aortic ring assay. In the murine model, a significant reduction in tumor size and weight (0.910.21 g) and a substantial increase in helper T cells (5-fold) and cytotoxic T cells (7-fold) were observed in the kefir water–treated group. The mechanism of action of kefir water was further demonstrated at the molecular level by conducting real time polymerase chain reaction and proteomic profiler. These findings suggest that kefir water contains largely Lactobacillus species and possesses antioxidant property. Kefir water inhibited tumor proliferation in vitro and in vivo mainly through cancer cell apoptosis, immunomodulation by stimulating T helper cells and cytotoxic T cells, and anti-inflammatory, antimetastatic, and antiangiogenesis effects. This study brought out the potential of the probiotic beverage kefir water in cancer treatment.